2015
DOI: 10.12968/bjcn.2015.20.9.451
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control in home nursing: case study of four organisations in Australia

Abstract: It is imperative that policy is developed to support nurses' decision making and practices as they address infection control challenges in the community environment. Ensuring staff are well-supported with resources, education, policy, and guidelines to address these challenges is important for the delivery of safe and high-quality care in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Effective PPE must be available for midwives based in the community for antenatal appointments and for assisting births [ 6 ]. Studies of infection control and personal protective equipment (PPE) in home healthcare have focused on hospital-in-the-home, where healthcare workers are caring for unwell people and often doing regular invasive procedures [ 21 , 22 ] rather than in the context of pregnancy care. Maintaining infection control in the home environments can be more difficult and this is even more so during a pandemic when PPE is a heightened issue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective PPE must be available for midwives based in the community for antenatal appointments and for assisting births [ 6 ]. Studies of infection control and personal protective equipment (PPE) in home healthcare have focused on hospital-in-the-home, where healthcare workers are caring for unwell people and often doing regular invasive procedures [ 21 , 22 ] rather than in the context of pregnancy care. Maintaining infection control in the home environments can be more difficult and this is even more so during a pandemic when PPE is a heightened issue [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining infection control in the home environments can be more difficult and this is even more so during a pandemic when PPE is a heightened issue [ 23 ]. For midwives this may be weighing scales and bags for example that will be taken from house to house [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taking into account the opinions of the medical community who are concerned about the continued occurrence of infectious diseases [69,70], it is necessary to prepare operational guidelines and evaluation guidelines suitable for the situation and conditions of public spaces that can respond to infectious diseases in the future. In an existing study, an Australian case presented a manual on procedures, education and worker training, and a monitoring system to provide care to clients at the time of MERS [71], and the elderly at home in response to this COVID-19 As in the case of the publication of rules for providing meal services for children [72], specific operational guidelines and appropriate public space evaluation guidelines should be prepared so that public spaces can provide services even in an infectious disease situation. In addition, as the provision of non-face-to-face services such as phone safety checks increases, work standards for telecommuting, etc., should be revised together.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of a survey to assess awareness of evidence published in Cochrane Reviews reported low knowledge among nurses [57], indicating a disconnect between review recommendations and consistency of practice [17]. However, this lack of engagement may also extend to Clinical Practice Guidelines, with evidence suggesting nurses prefer to consult with colleagues or rely on their intuition or beliefs [58][59][60][61], rather than evidence-based recommendations to inform clinical decision-making. Additional barriers such as: a lack of basic research education [62]; time constraints in busy clinical settings [63,64]; and limited support from senior nurses with knowledge and experience in research [65], also contribute to nurses' negative attitude to pressure injury prevention [66,67], resulting in low-value care [58,68].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this does not invalidate the relationship between the use of widely accepted practices to prevent and treat PI in health settings. Rather it signals the need for high quality research and ultimately greater emphasis on multi-faceted and tailored implementation strategies, that focus on methods to improve adoption, sustainment, and scale-up of interventions that bridge the gaps in clinicians' decision-making and practice [20,[59][60][61].…”
Section: Discussionmentioning
confidence: 99%